Companding techniques for SC-FDMA and sensor network applications. Issue 3 (2nd July 2020) - Abd El-Rahman, Amal F; Ahmed, Rania A; Abd Elnaby, Mustafa M.; Khamis, Salah; Napoleon, Sameh; Abd-Elnaby, Mohammed; Ahmed, Zeinab A; El-Rabaie, El-Sayed M.; Abd El-Samie, Fathi E.
ABSTRACT: The large Peak-to-Average Power Ratio (PAPR) is a serious problem in wireless communication systems for mobile and sensor network applications. This paper presents efficient non-linear techniques to solve the large PAPR problem in Single-Carrier Frequency Division Multiple Access (SC-FDMA) system and Wireless Sensor Network (WSN) systems. The performance of the proposed techniques is investigated over a realistic channel model. Simulation results reveal PAPR reduction while preserving low Bit Error Rate (BER) levels.